Adolescents' Mental Health: Can Memorizing The Qur'an Affect It? - Wardani, Riastuti Kusuma; Maulidia, Rani Dwi Jayanti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: The prevalence of mental health problems among adolescents is increasing. One way to improve mental health and help relieve stress is through memorizing the Quran. Objective: To determine the relationship between Quran memorization activities and other factors on adolescents’ mental health at Madrasah Tsanawiyah (MTs) Negeri 42 Jakarta in 2024. Methods: This quantitative research uses a cross-sectional design. Data were analyzed using the chi-square test with a sample of 107 respondents selected through proportional random sampling. Results: Students who experienced mental health problems, as assessed by the SDQ 20 questionnaire screening for ages 11-18 years, showed that 55.1% were in the abnormal category and 36.4% in the borderline category. There was a significant relationship between Quran memorization activity (P-value = 0.024) and social environment (P-value = 0.001) with mental health. However, counseling and genetic guidance services did not show any significant relationship with mental health (P-value > 0.05). Conclusion: The study suggests that schools can support students’ mental health through meetings, counseling, Quran activities, and guidance from teachers. It is recommended to implement mental health screening programs at schools, provide spiritual and mental guidance, create Quran memorization award programs, and promote mental health education. Encouraging students to engage in positive activities can also help improve their mental well-being.